Large language models’ capabilities in responding to tuberculosis medical questions: testing ChatGPT, Gemini, and Copilot - Meisam Dastani; Jalal Mardaneh; Morteza Rostamian (Scientific Reports, 2025)
Abstract This study aims to evaluate the capability of Large Language Models (LLMs) in responding to questions related to tuberculosis. Three large language models (ChatGPT, Gemini, and Copilot) were selected based on public accessibility criteria and their ability to respond to medical questions. Questions were designed across four main domains (diagnosis, treatment, prevention and control, and disease management). The responses were subsequently evaluated using DISCERN-AI and NLAT-AI assessment tools. ChatGPT achieved higher scores (4 out of 5) across all domains, while Gemini demonstrated superior performance in specific areas such as prevention and control with a score of 4.4. Copilot showed the weakest performance in disease management with a score of 3.6. In the diagnosis domain, all three models demonstrated equivalent performance (4 out of 5). According to the DISCERN-AI criteria, ChatGPT excelled in information relevance but showed deficiencies in providing sources and information production dates. All three models exhibited similar performance in balance and objectivity indicators. While all three models demonstrate acceptable capabilities in responding to medical questions related to tuberculosis, they share common limitations such as insufficient source citation and failure to acknowledge response uncertainties. Enhancement of these models could strengthen their role in providing medical information.